"Being Alone and Expectations Lost": A Realist Theory of Neighborhood Context, Stress, Depression, and the Developmental Origins of Health and Disease. (March 2018) - Eastwood, John; Kemp, Lynn; Jalaludin, Bin
We have previously reported on the findings of a critical realist concurrent triangulated mixed method multilevel study that sought to identify and explain complex perinatal contextual social and psychosocial mechanisms that may influence the developmental origins of health and disease. That study used both emergent and construction phases of a realist explanatory theory building method. The purpose of this article is to present the thesis, theoretical framework, propositions, and models explaining neighborhood context, stress, depression, and the developmental origins of health and disease. The analysis draws on an extensive extant literature; intensive (qualitative), extensive (quantitative), and multilevel studies used for phenomena detection, description, and emergent phase theory development; and the abductive and retroductive analysis undertaken for the theory construction phase. Global, economic, social, and cultural mechanisms were identified that explain maternal stress and depression within family and neighborhood contexts. There is a complex intertwining of historical, spatial, cultural, material, and relational elements that contribute to the experiences of loss and nurturing. Emerging is the centrality of social isolation and " expectation lost " as possible triggers of stress and depression not only for mothers but possibly also for others who have their dreams shattered during life's transitions. The thesis: In the neighborhood spatial context, in keeping with critical realist ontology, global-economic, social, and cultural-level generative powers trigger and condition maternal, psychological, and biological-level stress mechanisms, resulting in the phenomenon of maternal depression and alteration of the infants' developmental trajectory.